CTA Annual Report 2012: Raising the bar - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2013)
For CTA, 2012 proved to be another exciting and fruitful year. Highlights included bolstering capacity in key areas, building partnerships and a major international conference on value chain development. Organised with the UN Economic Commission for Africa and 18 other organisations, the conference attracted 70 countries and provided an excellent opportunity to share lessons, create awareness and collaborate with the private sector. The annual report showcases CTA’s work on policy processes, inclusive agri-business, knowledge management and ICT for agriculture.